Tecendo Memórias - trajetórias e conduções de narrativas femininas em processo teatral - Miranda, Ana Beatriz (2023)
This research, of an autoethnographic nature, deals with a reflection on female silencing through women's memories. To do this, it was necessary to understand some historical landmarks, such as the Witch Hunt movement and colonialism in Brazil, fundamental events for understanding female silencing. During the research, memories of women in my family and memories of female artists in the city of Uberaba/MG were incorporated. With the first group I conducted interviews with elderly women in my family, which served as inspiration for the creation of a short film. With the last group, I carried out practical research, in which I used free writing as a method to collect the memories of women artists, which was later explored in a process of creating individual and collective scenes.